2010
DOI: 10.1007/s10812-010-9318-4
|View full text |Cite
|
Sign up to set email alerts
|

Power and lasing threshold for longitudinally pumped lasers with intracavity raman self-conversion

Abstract: A method is developed for calculating the power and lasing threshold for longitudinally pumped lasers with intracavity Raman conversion. The theoretical analysis is based on equations for the powers of light beams in the cavity. Expressions for the power and lasing threshold of a Raman laser with self-conversion as functions of the parameters of the active medium, cavity, and pumping, taking into account the overlap of all the interacting beams, are derived and analyzed.Keywords: Raman conversion, Raman laser,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…The equations obtained previously [10] form the basis for discussing the above experimental results. It is noteworthy that the conditions for applying them were fulfilled in the experiment.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…The equations obtained previously [10] form the basis for discussing the above experimental results. It is noteworthy that the conditions for applying them were fulfilled in the experiment.…”
Section: Introductionmentioning
confidence: 91%
“…This was 12% of the diode pumping power. The equations obtained previously [10] and estimates of the focal lengths of thermal lenses induced in the composite crystal by transformations of the pumping radiation into the primary laser radiation and this radiation into the Stokes component were used to analyze the experimental results. It was shown that thermal effects play a very important role in forming the spatial structure and diffraction losses of the beams in a cavity with plane mirrors.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations